The association between the ratio of monocytes:lymphocytes at age 3 months and risk of tuberculosis (TB) in the first two years of life - Naranbhai, V; Kim, S; Fletcher, H; Cotton, M; Violari, A; Mitchell, C; Nachman, S; McSherry, G; Mcshane, H; Hill, A; Madhi, SA (BioMed Central, 2014)
BACKGROUND: Recent transcriptomic studies revived a hypothesis suggested by historical studies in rabbits that the ratio of peripheral blood monocytes to lymphocytes (ML) is associated with risk of tuberculosis (TB) disease. Recent data confirmed the hypothesis in cattle and in adults infected with HIV. METHODS: We tested this hypothesis in 1,336 infants (540 HIV-infected, 796 HIV-exposed, uninfected (HEU)) prospectively followed in a randomized controlled trial of isoniazid prophylaxis in Southern Africa, the IMPAACT P1041 study. We modeled the relationship between ML ratio at enrollment (91 to 120 days after birth) and TB disease or death in HIV-infected children and latent Mycobacterium tuberculosis (MTB) infection, TB disease or death in HEU children within 96 weeks (with 12 week window) of randomization. Infants were followed-up prospectively and routinely assessed for MTB exposure and outcomes. Cox proportional hazards models allowing for non-linear associations were used; in all cases linear models were the most parsimonious. RESULTS: Increasing ML ratio at baseline was significantly associated with TB disease/death within two years (adjusted hazard ratio (HR) 1.17 per unit increase in ML ratio; 95% confidence interval (CI) 1.01 to 1.34; P = 0.03). Neither monocyte count nor lymphocyte counts alone were associated with TB disease. The association was not statistically dissimilar between HIV infected and HEU children. Baseline ML ratio was associated with composite endpoints of TB disease and death and/or TB infection. It was strongest when restricted to probable and definite TB disease (HR 1.50; 95% CI 1.19 to 1.89; P = 0.006). Therefore, per 0.1 unit increase in the ML ratio at three to four months of age, the hazard of probable or definite TB disease before two years was increased by roughly 4% (95% CI 1.7% to 6.6%). CONCLUSION: Elevated ML ratio at three- to four-months old is associated with increased hazards of TB disease before two years among children in Southern Africa. While significant, the modest effect size suggests that the ML ratio plays a modest role in predicting TB disease-free survival; its utility may, therefore, be limited to combination with existing tools to stratify TB risk, or to inform underlying pathophysiologic determinants of TB disease.